Tangshan—China's one time industrial pioneer striving for ecological excellence. (May 2017) - Li, Dongquan; Lan, G. Zhiyong; Kraeger, Patsy; Wei, Ming
Abstract: Tangshan is one of China's oldest industrial cities, indeed its developmental trajectory well reflects China's modern industrial history. However, what brought the city notoriety was a magnitude 7.8 earthquake in 1976, which killed 203, 555 people, severely injured 137, 753 more, and destroyed over 90% of the houses and roads overnight. Forty years later Tangshan has been rebuilt into a city driven by up-to-date planning imperatives and high urban synergy which have resulted in an improved quality of life, attractive ecological environments and the urban leadership's enthusiasm for sustainable development. This paper discusses Tangshan's industrial history, painful lessons from the earthquake, and re-development, including the port of Caofeidian and the new town of Nanhu, as well as challenges and prospects for the future. Highlights: Tangshan is one of China's oldest industrial cities. Its developmental trajectory well reflects China's modern industrial history. Tangshan suffered an unusual magnitude 7.8 earthquake on July 28th, 1976, which killed 203, 555 people, severely injured 137, 753 more, and destroyed over 90% of the houses and roads overnight. Tangshan learned a painful lesson from that failed disaster forecast. Tangshan has set its objectives to become an ecological model. It faces further challenges. More work is needed.